User interface design for existing system monitoring application - Mishra, Prashamsa ([Espoo] : Metropolia Ammattikorkeakoulu, 2013)
Abstract: User interface design for existing system monitoring application. The main purpose of the project was to make use of elements of interface design to create an application. Another purpose was to see how Enoro (customer) Generis system (customer's internal system) merges with the web in particular application. The goal was to create an application web interface for existing System Monitoring application. ASP.NET framework with C# programming language, Enoro Generis System and user interface design elements were used for creating the application. The application serves Enoro's customers to monitor their servers and view the result via web interface. The application development is still ongoing. The final product was not aimed for this study but the thesis application well demonstrates the concept of final application. The application carries good importance to both Enoro and its customers regarding business values and system robustness monitoring and immediate problem fixing. The application also demonstrates how user interface design influences application's use. The concept of the application itself is important for users who can easily know what is going on in their systems regardless of their location and the platform they use.
Graafinen ja digitaalinen viestintätekniikka.
AMK-opinnäytetyö
Saantitapa: World Wide Web.
XLUETTELOITU
Kuvailu tarkistettu verkkojulkaisusta (30.07.2013).
Keywords: User interfaces (Computer systems).; käyttöliittymät